Leadership in the Time of Change - Marian Năstase (Revista de Management Comparat International)
Last years, the environment has placed more challenges for the organizations to cope with. The economic crisis brings new issues in the front of the leaders, forcing them to question again the ways of leading and the possibilities to get most of value from their human resources potential.